Evaluation of The Effect of Zinc Oxides Nanoparticles on Bacteria Activity And Biofilm Formation of Clinical Acinetobacter Baumannii (Journal of the College of Basic Education, 2026)
This study was conducted in the Mustansiriyah University, College of Science, laboratories of Department of Biology , from (November 2024 to January 2025) . A total of (120) samples were collected from different clinical sources, including burns, wounds, and urine and blood In addition to environmental samples from the hospital environment . Al-Imamain Al-Kadhimiya Hospital, Al-Karkh General Hospital, and the Medical City's teaching laboratories were among the participating hospitals. Every sample was cultivated on MacConkey Agar and Blood Agar media and incubated for the whole night at 37°C. Only 27 isolates were identified as Acinetobacter baumannii. All these isolates were identified and purified by culture on chromium agar, biochemical tests, and the use of the 16S rRNA gene. Zinc oxide nanoparticles were then biosynthesized from Pseudomonas aeruginosa and hydrated zinc sulfate (ZnSO4.7H2O). If zinc sulfate is reduced to form zinc oxide nanoparticles. The properties of the resulting nanomaterial were studied using different devices, including UV, EDX , XRD, and SEM. The results of these devices showed up the formation of pure ZnO Nps in various shapes and sizes ranging between 20 to 100 nm . The ability of synthesized nanoparticles to inhibit Acinetobacter baumannii bacteria was studied at concentrations of (0.4, 0.6, 0.8, 1, 1.2, 1.4, and 1.6) mg/ml. It was found that the effectiveness of ZNO NPS increased with increasing concentrations The highest percentage was at a concentration of 1.6 (94%).The efficiency of the synthesized nanomaterial in inhibiting some virulence factors was tested. The ability of ZnO Nps On the Inhibition of biofilms formation in Acinetobacter baumannii bacteria was studied. A range of different concentrations (0.1, 0.2, 0.3, 0.4, and 0.5) mg/ml were used. The concentration of 0.4 and0.5 showed the highest biofilm inhibition .